Ergodic Capacity of MIMO Correlated Channels in Multipath Fading Environment with known Channel State Information - Mir Muhammad Lodro; Muhammad Hanif Abro (Institute of Advanced Engineering and Science, 2012)
In this paper we have evaluated the performance of Multiple Input Multiple Output (MIMO) channels in fading environment. Both cases of correlated and uncorrelated MIMO channels are considered under the condition when Channel State Information (CSI) is not known at transmitter and CSI is known at receiver side. We have compared the capacity of 2x2, 3x3 and 4x4 MIMO channels and have shown that capacity increases linearly with increase in the number of antennas at transmitter and receiver side. Increase in the channel capacity is observed because of the uncorrelated channel paths Correlation among the the signals is dependent on the antenna structure and properties and number of the scatterers in the environment. Antenna structure includes the number of elements, the inter-element distance, Angle of Arrival (AOA) and Direction of Arrival (DOA). Additionaly, Correlation increases with the number of scatterers, their distribution, location and degree of movement. Signals with same spatial signature received are considered correlated which reduces the channel capacity. In sum, correlation among the sub-channels causes the degradation in the spectral efficiency of MIMO channels.DOI:http://dx.doi.org/10.11591/ijece.v2i5.1510